Analisis Diversifikasi Dan Ukuran Perusahaan Terhadap Return Pada PT. Lampung Distribusindo Raya Tbk Lampung Selatan - Septiani, Ana; Lelawati, Nina; Angelina, Dyas (Jurnal Manajemen DIVERSIFIKASI, 2023)
This study aims to determine the effect of diversification and firm size on returns at PTLampung Distributionsindo Raya TBK South Lampung. This research is quantitative, wherequantitative research is research that uses data types that can be measured or calculateddirectly through the measurement of research variables using numbers. The analyticaltechnique used in this study is a path analysis technique. The results show that diversificationhas a positive and significant effect on stock returns, which means that if the company ismore diversified, the stock returns will increase. The size of the company has a positive andsignificant effect on stock returns, which indicates that the higher the size of the company, thehigher the stock returns